2018
DOI: 10.1053/j.ajkd.2017.11.020
|View full text |Cite|
|
Sign up to set email alerts
|

Arteriovenous Fistula Maturation in Prevalent Hemodialysis Patients in the United States: A National Study

Abstract: We identified numerous associations between AVF maturation and patient-level factors in a recent national sample of US hemodialysis patients. After accounting for these patient factors, we observed substantial differences in AVF maturation across some ESRD networks, indicating a need for additional study of the provider, practice, and regional factors that explain AVF maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 57 publications
6
107
2
5
Order By: Relevance
“…The respective numbers after 2 months were 98% (Japan), 79% (Europe), and 36% (US). In a recent study from the United States, Woodside et al [5] used CrownWeb data to characterize time to the first use of newly created AVF as surrogate for successful AVF maturation. The authors identified 45,087 new AVFs that were placed in 39,820 prevalent HD patients in 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective numbers after 2 months were 98% (Japan), 79% (Europe), and 36% (US). In a recent study from the United States, Woodside et al [5] used CrownWeb data to characterize time to the first use of newly created AVF as surrogate for successful AVF maturation. The authors identified 45,087 new AVFs that were placed in 39,820 prevalent HD patients in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…An AVF is favored due to its advantage over CVC usage with respect to sur- vival outcomes, hospitalization rates, and cost to the healthcare system [1][2][3][4]. Notwithstanding this evidence, most US incident patients start HD using a CVC [5][6][7][8]. Even though the use of AVF has notably improved in prevalent patients, the initiation of HD with an AVF continues to be low.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the median time to maturation was 114 days, while the ADR reported a median time to maturation of 111 days [1]. A recent analysis of prevalent HD patients in USRDS with a new AVF observed a median time to maturation of 111 days with 36.2% of AVF having no evidence of use in CROWNWeb [19]. However, no post-placement outcomes other than maturation were evaluated and the study did not include AVG placements.…”
Section: Doi: 101159/000495355mentioning
confidence: 99%
“…Patients initiating dialysis with a mature or maturing AVF or AVG may be clinically and demographically different from patients initiating dialysis with a catheter alone, which may impact placement-related outcomes such as maturation and abandonment [19,23]. To evaluate whether patients with a mature or maturing AVF or AVG at first dialysis were different than patients initiating dialysis with a catheter alone, demographic and clinical characteristics were stratified by access at first dialysis (online Suppl.…”
Section: Doi: 101159/000495355mentioning
confidence: 99%
“…Also, access failure remained a common reason for hospitalization of end‐stage renal disease (ESRD) patients, the exact opposite of the intended goal . Another obscure factor recently identified is the disparity in fistula maturation rate across ESRD networks, indicating a need for additional study of the provider, practice, and regional factors that explain AVF maturation …”
Section: Failure Of Various Access Types To Meet Reliable Access Expementioning
confidence: 99%